(untitled) (The Pakistan Development Review, 2003)
The main objective of this study is to estimate the input elasticities of production for poor and non-poor farms. The study estimates the stochastic frontier production function. The results show that the elasticities of production differ for poor and non-poor farms. The production elasticity of land is substantially higher on rich farms as compared to the farms belonging to poor farmers. This implies higher returns on investment on land by the rich farmers. The salinity/sodicity problem and the tail-end location of the plot adversely affect farm productivity and efficiency, particularly at the poor farms. Moreover, the average cost of the existence of technical inefficiencies is about 43 percent in terms of loss in output, with wide variations across farms ranging from 17 percent to 62 percent. The study further concludes that the least efficient group is not only operating far below the frontier but it also operates at the lower portion of the production frontier. Consequently, increasing access to the inputs would likely raise productivity and reduce poverty. The results imply that the land distribution using the notion of land reforms in favour of poor/small farmers in the presence of existing farm structure, rural infrastructure, and the weak farm-supporting institutions is not expected to raise farm productivity and reduce poverty among the poor farmers. The results call for a strong and active role of the government in close partnership with the private sector to initiate income-generating activities and inputs supply chains in the rural areas to break the nexus of poverty, land degradation, and low agricultural productivity.